PENGARUH ONLINE REVIEW DALAM KANAL YOUTUBE FEMALE DAILY NETWORK TERHADAP MINAT BELI PRODUK SKINCARE OLEH REMAJA PEREMPUAN - Sofia Diva Widiarti (2023)
The increasing role of information and communication technology in everyday life has created a new media culture or commonly referred to as the era of the industrial revolution 4.0. One of the social media used in finding information is Youtube. One of the phenomena that is widely discussed on social media is the "GlowUp Challenge". Female Daily Network is a beauty review platform that provides recommendations on various skincare products. So from these problems, the purpose of this study was to analyze the influence of online reviews on the Youtube Female Daily Network channel on the interest in buying skincare products by teenage girls. The theory used in this research is cognitive response theory. This study uses a quantitative approach, explanative type with survey methods. The collection of research data was obtained from the results of distributing questionnaires to 100 respondents who were in accordance with the research criteria, then through validity and reliability tests. The research data were analyzed by looking at the results of data processing from simple linear regression tests, coefficient of determination tests, and hypothesis testing through the SPSS 26 program. Based on the results of the coefficient of determination test it was found that the value of variable X (online review) has a correlation with variable Y (purchase intention) of 71.4%, this is in line with the results of the hypothesis test which shows that the t-value is 15.662 > t-table, which is 1.660, which means that there is a significant and significant influence between online reviews on the Youtube Female Daily Network channel on interest in buying skincare products by teenage girls. This research is expected to be a reference source that can be developed better in the future.